Odpowiedzi

Najlepsza Odpowiedź!
2009-11-14T14:24:23+01:00
A) układ równań
x^2+(y-4)^2=25
y=-7x+29
podstawiamy za y do 1 równania
x^2+(-7+25)^2=25
50x^2-350x+600=0 /:50
x^2-7x+12=0

Δ=49-48=1

x1=-4 => y=57 A(-4,57)
x2=3 => y=8 B(3,8)

b) |AB|=√(-4-3)^2 + (57-8)^2= √49 + 2401=√2450≈49,5
4 2 4
2009-11-14T15:30:46+01:00
X² + (y - 4)² = 25
x² + y² - 8y + 16 - 25 = 0
Za y podstawiamy -7x +29 z równania prostej:
x² + (29 - 7x)² - 8(29 - 7x) - 9 = 0
x² + 841 - 406x + 49x² - 232 + 56x - 9 = 0
50x² - 350x + 600 = 0 / :50
x² - 7x + 12 = 0
Δ = 49 - 48 = 1
√Δ = 1
x₁ = (7-1)/2 = 3 => y = 8 (z równania prostej)
x₂ = (7+1)/2 = 4 => y = 1 - || -
A = (3, 8)
B = (4, 1)
b)
|AB| = √[(4 - 3)² + (1 - 8)²] = √50 = 5√2
2 5 2